Aspen Soils Retain More Dissolved Organic Carbon Than Conifer Soils in a Sorption Experiment - Boča, Antra; Jacobson, Astrid R.; Van Miegroet, Helga (Frontiers in Forests and Global Change, 2020)
Tree species effects on soil organic carbon (SOC) have been much debated but few clear patterns have emerged so far. One example of a differing tree species effect on SOC are aspen forests in North America, which have been found to have more stable SOC than adjacent conifer forest stands. An important source for the formation of stable organo-mineral complexes in soil is dissolved organic carbon (DOC). DOC concentrations in minerals soil are often higher under the thick O-horizons of conifer forests than under aspen forests, but this does not correspond to more stable mineral SOC. This suggests that instead of DOC concentration DOC quality could be driving the observed differences in SOC. Therefore, we quantified the retention of contrasting forest detritus DOC in soils. Using a batch sorption experiment approach, we compared the retention of detritus leachates from four sources – aspen leaves (AL), aspen roots (AR), conifer (subalpine fir) needles (CN), and conifer (subalpine fir) roots (CR) – on soils sampled under aspen and conifer (subalpine fir and Douglas fir) overstories. The calculated sorption isotherms showed a higher retention of AL DOC than AR DOC, as indicated by all four sorption parameters – k and n (curve-fitting parameters), null point concentration (NPC; net sorption = net desorption), and endpoint (EP, retention at the highest initial DOC concentration). Leachates from CN and CR showed very similar retention behavior, and between the two species the retention of root leachates was more similar than the retention of foliage leachates. Soils sampled from aspen forests showed higher affinity for new DOC than conifer soils (higher sorption rate (n), lower NPC, and higher EP) regardless of the DOC source. The findings suggest that the higher DOC sorption on aspen soils might be a major driver for more stable SOC under aspen stands in North America.